Analysis of the genetic variation in mitochondrial DNA, Y-chromosome sequences, and MC1R sheds light on the ancestry of Nigerian indigenous pigs - Adeniyi C. Adeola; Olufunke O. Oluwole; Bukola M. Oladele; Temilola O. Olorungbounmi; Bamidele Boladuro; Sunday C. Olaogun; Lotanna M. Nneji; Oscar J. Sanke; Philip M. Dawuda; Ofelia G. Omitogun; Laurent Frantz; Robert W. Murphy; et al. (Genetics Selection Evolution, 2017)
Abstract Background The history of pig populations in Africa remains controversial due to insufficient evidence from archaeological and genetic data. Previously, a Western ancestry for West African pigs was reported based on loci that are involved in the determination of coat color. We investigated the genetic diversity of Nigerian indigenous pigs (NIP) by simultaneously analyzing variation in mitochondrial DNA (mtDNA), Y-chromosome sequence and the melanocortin receptor 1 (MC1R) gene. Results Median-joining network analysis of mtDNA D-loop sequences from 201 NIP and previously characterized loci clustered NIP with populations from the West (Europe/North Africa) and East/Southeast Asia. Analysis of partial sequences of the Y-chromosome in 57 Nigerian boars clustered NIP into lineage HY1. Finally, analysis of MC1R in 90 NIP resulted in seven haplotypes, among which the European wild boar haplotype was carried by one individual and the European dominant black by most of the other individuals (93%). The five remaining unique haplotypes differed by a single synonymous substitution from European wild type, European dominant black and Asian dominant black haplotypes. Conclusions Our results demonstrate a European and East/Southeast Asian ancestry for NIP. Analyses of MC1R provide further evidence. Additional genetic analyses and archaeological studies may provide further insights into the history of African pig breeds. Our findings provide a valuable resource for future studies on whole-genome analyses of African pigs.